Malaysian Youth Motivational Factors of Film-Induced Tourism for Indonesian Film - Zulkifli, Nurul Deeyana; Rahman, Nur Hidayah Abd (Journal of Indonesian Tourism, Hospitality and Recreation, 2021)
There are lots of efforts require in maintaining the sustainability of the tourism business, including promoting and marketing tourism destinations world widely. One of the alternatives recently used by the tourism industry around the world in promoting and marketing the places is through film tourism. In Indonesia, the film of Laskar Pelangi sparked the tourism industry in Indonesia. However, research on motivational factors of film-induced tourism in Indonesian film is limited. Thus, the study aims to identify the motivational factors that influence Malaysian youth to visit Indonesia after watching Indonesian films. To achieve the aim, the push and pull factors of film-induced tourism for Indonesian film have been investigated. This study using quantitative method for collecting the data and the questionnaires have been distributed to Malaysian youth who had watched Indonesian films as the target respondents. A total of 117 respondents were influenced to visit Indonesia after watching Indonesian films have participated in this research. This results show that novelty, entertainment and film location influenced Malaysian youth to visit Indonesia. The study suggests exploring other factors, such as accessibility, which could influence Malaysian youth to visit film location. Thus, this study provides a clear insight to research academic on motivational factors from Indonesian films that influence Malaysian youth to visit Indonesia. Further, it gives benefit to the tourism and film industry in Indonesia.Keywords: Film-Induced Tourism, Indonesian Film, Travel Motivation, Push and Pull Factors